2020
DOI: 10.1108/ecam-11-2018-0527
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a strategy map for coastal urban project success using the balanced scorecard method

Abstract: PurposeThis study aims to develop a strategic framework for the success of coastal urban projects in Vietnam, which is one of the Asia Pacific countries significantly affected by climate change.Design/methodology/approachA questionnaire was used to collect data from practitioners in Vietnam. Principal component analysis (PCA) technique was used to identify critical success factors (CSFs) of coastal urban projects. A strategy map for the success of coastal urban projects was also proposed using the balanced sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 128 publications
0
9
0
Order By: Relevance
“…Suppliers represent all stakeholders who provide PP with services or materials. This factor is important in the achievement of (Abbasi et al, 2020;Arbabi et al, 2020;Bai et al, 2018;Yildiz et al, 2020) D22 project portfolio Lean culture D23 project portfolio internal communication D3 process data D31 Data preservation integrity (Huynh et al, 2020;Jonas, 2010) D32 Historical experience learning Table 2.…”
Section: Results Of Influencing Factor Network Constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Suppliers represent all stakeholders who provide PP with services or materials. This factor is important in the achievement of (Abbasi et al, 2020;Arbabi et al, 2020;Bai et al, 2018;Yildiz et al, 2020) D22 project portfolio Lean culture D23 project portfolio internal communication D3 process data D31 Data preservation integrity (Huynh et al, 2020;Jonas, 2010) D32 Historical experience learning Table 2.…”
Section: Results Of Influencing Factor Network Constructionmentioning
confidence: 99%
“…The implementation of a PP may be restricted or supported by government policies, largely depending on the corresponding policy response (Lin et al, 2019). In recent years, PP has increasingly focused on sustainable development goals related to society and the government, such as the ecological environment and social responsibility (Huynh et al, 2020).…”
Section: Results Of Influencing Factor Network Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the map shows only those factors which have connections with the strategic factors (Figure 2.). Performance measurement in the idea of a balanced scorecard is based on a structured set of factors (Huynh, 2020). As a result of the research, three of the four BSC perspectives were identified, and their list was developed accordingly.…”
Section: Factor Maps and Correlationsmentioning
confidence: 99%